Angiotensin II sustains brain inflammation in mice via TGF-β - Lanz, Tobias; Ding, Zhaoqing; Ho, Peggy P.; Luo, Jian; Agrawal, Ankur N.; Srinagesh, Hrishikesh; Axtell, Robert; Zhang, Hui; Platten, Michael; Wyss-Coray, Tony; Steinman, Lawrence (The journal of clinical investigation, 2010)
The renin-angiotensin-aldosterone system (RAAS) is a key hormonal system regulating blood pressure. However, expression of RAAS components has recently been detected in immune cells, and the RAAS has been implicated in several mouse models of autoimmune disease. Here, we have identified Ang II as a paracrine mediator, sustaining inflammation in the CNS in the EAE mouse model of MS via TGF-β. Ang II type 1 receptors (AT1Rs) were found to be primarily expressed in CNS-resident cells during EAE. In vitro, astrocytes and microglia responded to Ang II treatment by inducing TGF-β expression via a pathway involving the TGF-β–activating protease thrombospondin-1 (TSP-1). TGF-β upregulation in astrocytes and microglia during EAE was blocked with candesartan (CA), an inhibitor of AT1R. Treatment of EAE with CA ameliorated paralysis and blunted lymphocyte infiltration into the CNS, outcomes that were also seen with genetic ablation of AT1Ra and treatment with an inhibitor of TSP-1. These data suggest that AT1R antagonists, frequently prescribed as antihypertensives, may be useful to interrupt this proinflammatory, CNS-specific pathway in individuals with MS.